Key Parameter Design and Experimental Analysis for Peelable Seedling Belts in Sweet Potato Transplanting Systems - Youhao Wei; Kun Li; Minjuan Hu; Bing Qi; Yao Ji; Wenyi Zhang; Wei Yan (Applied Sciences)
Sweet potato is essential for food security, but its transplanting efficiency is currently low. To improve this, we developed a belt-type transplanter that uses seedling belt technology for automated feeding, increasing efficiency by over 25%. The use of the seedling belt is key to significantly enhancing the transplanter’s efficiency. Building on seedling belt feeding, we designed a “trumpet-shaped” staggered detachable seedling belt using LDPE film. Seedlings are fixed at intervals between two film layers via thermal bonding points. Mechanical analysis showed the optimal peeling strength is 13.2 N, ensuring smooth seedling transport during transplanting. Peeling strength depends on the heat sealing temperature, time, and pressure. To optimize these parameters, we designed an experimental device and conducted single-factor experiments to determine their effects on the peeling strength and establish reasonable ranges. Results show that, at a peeling strength of 13.2 N, the thermal bonds separate smoothly without tearing the film. A three-factor, three-level orthogonal experiment further optimized the heat sealing parameters, concluding that, at 140 °C, 1.2 s, and 0.4 MPa, the average peel force of the seedling tapes obtained from the experiments was 14.31 N, at which point the peeling effect was optimal.